A Temporal and Dynamic Approach to Enjambments in French Versified Poetry from the 17th to the late 19th Century - Éliane Delente (Studia Metrica et Poetica)
This study is about enjambments, rejets and contre-rejets in French metrical poetry. No study explains why these constructions are seen as characteristic of poetry. Moreover, the common approach in terms of (mis)alignment between metrical and prosodic or syntactic structure leaves a number of unanswered questions. Why meter is studied only in its relationships with prosody or syntax, leaving many other aspects of discourse unexamined? When the meaning in a line straddles the line break to continue into the next line, which line is concerned by the enjambment? the first, the second, or both? Does enjambment constitute a homogeneous category?